Association of Dermatological Conditions of External Ear with the Use of Cotton Buds - Ahmed, Salahuddin; Zaheer, Syed Atif Imran; Shabbir, Syed Muhammad Asad; Rao, Sibghatullah; Islam, Tauhidul; Ahmed, Bashir (Journal of Enam Medical College, 2014)
Background: The habit of cleaning the external auditory canal with cotton buds is a common practice of the masses. It has strong association with neurodermatitis and contact dermatitis of the external ear. It is also associated with acute otitis externa, rupture of tympanic membrane causing bleeding and temporary hearing loss in some cases. In many cases the injury will heal but damage to minuscule bones deep inside the ear can cause permanent deafness. Objective: The objective of this study was to determine the association of dermatological condition of external ear with the use of cotton buds. Materials and Methods: This case control study was done from January to October 2012 in the Ear Nose Throat Department of Pakistan Level III Hospital, Darfur, Sudan. Sixty seven patients with dermatological diseases of external ear were cases and 83 subjects without dermatological diseases of external ear were selected as controls. Results: Among 67 cases, 58 were cotton bud users and among 83 controls only 29 were cotton bud users. Different types of dermatological diseases were neurodermatitis (34.32%), otitis externa (28.36%), contact dermatitis (26.87%) and wax impaction (8.95%). Ninety three percent of cotton bud users were ignorant of harmful effects of this bad habit. Conclusion: There is a strong association of dermatological diseases of external ear with the use of cotton bud which should be discouraged by fortifying the warning by manufacturers and health education at various educational levels. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20956 J Enam Med Col 2014; 4(3): 174-176